Elaboração de jogo digital como estratégia para o ensino de textos narrativos - Silva, José Maurício Santos da (2021)
Digital games can be adopted, in the Area of Letters, from an interdisciplinary theoretical framework, for example, involving digital educational technology, computer, narrative text and Digital Game-Based Learning. As we verified in the area literature, textual production is already a reality in the teaching of Portuguese language and literature using the elaboration of computer game. An example is the production of the narrative to be inserted in the history of each game, which involves textual genre knowledge, typology and the narrative elements for writing from paper until it is inserted in the electronic editor. This research is justified by not only for proposing the use of digital game, but the elaboration itself, which allows greater interaction using Portuguese language and narrative categories. This practice offers a greater number of interventions during the writing and rewriting process. We envision the use of a virtual game-making environment known as RPG Maker VX ACE for the narrative text insertion written by 10 elementary school students from a state public school in Fortaleza. The general objective was to develop the textual production ability in the narrative construction with writing, rewriting and a digital game elaboration. The specific objectives were to verify cohesion and coherence factors in the textual production process, analyze whether it contributes to the textuality construction, grammatical aspects, notatives and textual production strategies, configure the game with narrative development using its elements and evaluate learning, gameplay and technical aspects. Data collection and generation were performed in five stages, including the proposed application of the project in the first stage. The second stage corresponds to the diagnosis with the elaboration of two narrative maps and textual production related to the narrative. The third moment corresponds to the rewriting of the narrative in the wonderful tale genre. In the fourth phase, the game was set up with access to rpg maker VX ACE and the insertion of the text. The fifth phase considers the testing of the game in relation to its operation regarding aspects of learning, gameplay and technique. At the end of the process, it was verified that the narrative text production learning in the game elaboration is confirmed positive for 100% of the participants, observing the elaboration, produced texts’ insertion and the game as the text support elaborated collaboratively. Regarding the recognition of the narrative with the students’ active participation in the game construction with collaborative rewriting, the results show that the secondary hypothesis obtained a positive response to 90%, being just 10% of negative in 100% responses regarding the understanding of the game specifically for 9th grade students. It was possible to verify failures regarding cohesion factors and coherence in the first writing, resolved throughout the rewriting process. In conclusion, it was confirmed that the process contributed to the development of textual production with grammatical, notatory and production strategies built during the practice, including configuration of the game collaboratively with its positive functioning, for 100% of the participants.